2019
DOI: 10.1177/0300060519834459
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network model for prediction of hypoxemia during sedation for gastrointestinal endoscopy

Abstract: Objective This study was designed to assess clinical predictors of hypoxemia and develop an artificial neural network (ANN) model for prediction of hypoxemia during sedation for gastrointestinal endoscopy examination. Methods A total of 220 patients were enrolled in this prospective observational study. Data on demographics, chronic concomitant disease information, neck circumference, thyromental distance and anaesthetic dose were collected and statistically analysed. Results Univariate analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…Therefore our results agree substantially also with this report. Nevertheless, the present study's findings differ from those published by Geng et al [33] because they found no effect of age and ASA score on intraprocedural hypoxemia. These authors addressed only hypoxemia as an AE and did not consider some other important potentially predictive variables, such as in-hospital versus outpatient, the duration of the procedure, and the sedative drug association.…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore our results agree substantially also with this report. Nevertheless, the present study's findings differ from those published by Geng et al [33] because they found no effect of age and ASA score on intraprocedural hypoxemia. These authors addressed only hypoxemia as an AE and did not consider some other important potentially predictive variables, such as in-hospital versus outpatient, the duration of the procedure, and the sedative drug association.…”
Section: Plos Onecontrasting
confidence: 99%
“…In a recent study conducted by Geng et al [33] and based on a much smaller sample (220 cases), it was reported that hypoxemia occurring during GI endoscopy is favored by BMI, habitual snoring, and neck circumference. It is conceivable that snoring and neck circumference may be associated with a higher Mallampati score.…”
Section: Plos Onementioning
confidence: 97%
“…It has been proven that obesity (body mass index, BMI>30 kg/m 2 ) is an independent risk factor for sedation-related adverse events [34,35]. Obese patients' respiratory physiology has the following features: first, hypertrophic chest wall hypertrophy, decreased thoracic compliance, high respiratory resistance, and a propensity for respiratory muscle fatigue in obese patients; second, the airway anatomical structure in obese patients is changed, such as short neck, neck activity restriction, and fat deposition in the pharyngeal wall [31,36]; third, baseline oxygen consumption increased as body mass index grew, whereas functional residual gas and oxygen reserve dropped [37].…”
Section: Obesity Patientsmentioning
confidence: 99%
“…Patients with risk factors of hypoxemia (age > 60 years old, obesity, heart/respiratory failure, diabetes, hypertension, obstructive sleep apnea) and ASA 2 patients may benefit from a high nasal flow oxygenation (HFO) [20,21]. Patients with a high STOP-BANG score, are prone to develop adverse respiratory events and require more maneuvers to control airways [22 & ].…”
Section: Airway Managementmentioning
confidence: 99%